Assessing and Managing Large‐Scale Geochemical Impacts From Groundwater Replenishment With Highly Treated Reclaimed Wastewater. Issue 11 (6th November 2020) - Sun, Jing; Donn, Michael J.; Gerber, Philippe; Higginson, Simon; Siade, Adam J.; Schafer, David; Seibert, Simone; Prommer, Henning
Abstract: Reuse of wastewater through a combination of advanced wastewater treatment (AWT) and managed aquifer recharge (MAR) is an important water management option. As an integral part of any AWT‐MAR system, the geochemical compatibility of the recharged water with the targeted aquifer must be assessed to avoid groundwater quality deterioration. Although short‐term field experiments may uncover potentially concerning sediment‐water disequilibria, an advanced analysis is often required to understand the long‐term geochemical impacts of large‐scale MAR. Here, we develop and apply a pragmatic approach to upscale and verify the previously derived local‐scale geochemical understanding to the spatial and temporal scale required for assessing and managing large‐scale and long‐term impacts resulting from the recharge of AWT‐processed water. We use Australia's largest MAR scheme, in which aerobic, purified water is injected into deep, anaerobic, pyritic aquifers as an illustrative example. In this case, the local‐scale understanding was derived from a comprehensive field trial and the interpretation of the data through a trial‐scale high‐resolution reactive transport model (RTM). Based on (i) the trial‐scale RTM, (ii) new data from the early phase of the full‐scale MAR, and (iii) downscaling of an existing, regional‐scale flow model, we developed an upscaled RTM to assess two critical issues for the large‐scale groundwater replenishment of Perth deep aquifers, that is, the sustainability of native pH buffering processes and the dynamics of fluoride release and attenuation. In a final step we illustrate how the upscaled RTM can be applied to assess how changes in the AWT affect long‐term groundwater pH changes. Key Points: Data and models at multiple scales were integrated to assess the geochemical impact of managed aquifer recharge with recycled water Injection of aerobic water triggered pyrite oxidization, but native buffering capacity prevented groundwater acidification Injection of low‐salinity water triggered fluoride release, but sufficient attenuation occurred